2017
DOI: 10.1016/j.jconrel.2017.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Optical barcoding of PLGA for multispectral analysis of nanoparticle fate in vivo

Abstract: Understanding of the mechanisms by which systemically administered nanoparticles achieve delivery across biological barriers remains incomplete, due in part to the challenge of tracking nanoparticle fate in the body. Here, we develop a new approach for "barcoding" nanoparticles composed of poly(lactic-co-glycolic acid) (PLGA) with bright, spectrally defined quantum dots (QDs) to enable direct, fluorescent detection of nanoparticle fate with subcellular resolution. We show that QD labeling does not affect major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Particle systems serve to enhance total bioavailability of poorly soluble molecules, and enrichment of nanoparticles along the endothelial cells enables passive diffusion of hydrophobic drugs into the parenchyma (Cook et al, 2015;Medina et al, 2017). We and others have shown that nanoparticles can transfer small hydrophobic payloads through contact with cell membranes (Xu et al, 2009;Medina et al, 2017). Presumably this is the mechanism at work here.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Particle systems serve to enhance total bioavailability of poorly soluble molecules, and enrichment of nanoparticles along the endothelial cells enables passive diffusion of hydrophobic drugs into the parenchyma (Cook et al, 2015;Medina et al, 2017). We and others have shown that nanoparticles can transfer small hydrophobic payloads through contact with cell membranes (Xu et al, 2009;Medina et al, 2017). Presumably this is the mechanism at work here.…”
Section: Discussionmentioning
confidence: 91%
“…Our lab previously demonstrated that delivery of drugs from polymeric nanoparticles can improve the efficacy of therapeutic candidates while reducing toxicity for the treatment of intracranial tumors via enhancements in bioavailability (Zhou et al, 2013;Cook et al, 2015;Householder et al, 2015Householder et al, , 2018. We have previously studied the fate of intravenously administered nanoparticles and encapsulated payloads in the central nervous system, demonstrating that delivery of hydrophobic payloads to the brain and spinal cord can be achieved even if the nanoparticles have not been designed for BBB passage (Cook et al, 2015;Medina et al, 2017). Particle systems serve to enhance total bioavailability of poorly soluble molecules, and enrichment of nanoparticles along the endothelial cells enables passive diffusion of hydrophobic drugs into the parenchyma (Cook et al, 2015;Medina et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one example, scientists isotopically-barcoded silver nanoparticles with different functional peptides to evaluate potential targeting ligands [43]. Another group has used quantum dots to barcode polymeric nanoparticles; in vivo screens were performed to understand how nanoparticle surface modifications altered delivery through the blood brain barrier [44]. …”
Section: Nanoparticle Barcoding Enables Simultaneous Analysis Of >100mentioning
confidence: 99%
“…PLGA nanoparticles can be used in diagnostic and therapeutic imaging by the addition of the imaging moieties during the particle synthesis. To date, large efforts have been devoted to conjugating PLGA with semiconducting quantum dots and organic dyes to create photoluminescent PLGA nanocarriers [9][10][11]. However, conventional approaches for physically blending imaging probes within the nanoparticles can lead to incomplete conclusions or misinterpretations on the nanoparticles' biodistribution and fate [12,13].…”
Section: Introductionmentioning
confidence: 99%